The Role of International Criminal Law in Violations of the Environment During Armed Conflict - AL-DLABEEH, Abedalrzag; ALSHARQAWI, Ahmad Hussein; AL KLOUB, Rami; KARABSHEH, Abdel-Kareem Ottallah (Journal of Environmental Management and Tourism, 2022)
The issue of protecting and preserving the environment is a great responsibility that falls on the shoulders of the state in all circumstances and conditions, whether in times of peace or in times of war, and there is no doubt that the commitment to preserving the environment becomes more necessary in times of war . The importance of international humanitarian law emerges during armed conflicts, as it is the applicable law, and as it is known that the environment in times of armed conflicts is exposed to major violations that may exceed those to which it is exposed in times of peace . The protection of the environment in international humanitarian law is represented in principles that the conflicting parties must observe their provisions and abide by in such circumstances. The most important of these principles is restricting the rights of belligerents, the principle of prohibiting unjustified pain, the principle of distinction between military objectives, and the principle of proportionality between them .